(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the relationship between smile characteristics and occlusion types according to Angle classification in first-year students at the University of Medicine and Pharmacy, Vietnam National University, Hanoi in 2022. Method: A cross-sectional study design on 96 students, aged 18-20. Data were collected through clinical examination, photography, observation of research subjects and analysis on SPSS software. Results: The height of the upper lip curve in the class II occlusion group was larger than that of the class I and class III occlusion groups. Smile height and mouth width had similar results between occlusion types; the class II canine occlusion had the highest rate of high smile lines; the class III canine occlusion group had the highest rate of low smile lines. Conclusion: There is a relationship between smile characteristics and types of occlusions according to Angle classification in first-year students; a larger sample size study is needed.